HYDROCRAKING OF HEAVY DISTILLATE INTO CLEAN DIESEL OIL USING Ni-Mo/Al2O3 CATALYST - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2000)
Diesel oil is high pollution fuel and the quality of this fuel must he improved to obtain clean diesel oil Crude oil production and its quality tend to decrease. Light fuel oil demand rate is higher than that of residual fuel. Diesel oil produced in the refineries generally consists of predominantly straight-run diesel oil: however, compounds such as thermally and catalytically cracked diesel oils are sometimes included. The quality of straight-run diesel oil, such as hydrocarbon types and sulfur content, will in general reflect the nature of crude oil. Cracked stocks either thermal or catalytic cracked diesel oils, contain higher percentage of aromatic, olefin and sulfur contents and these cracked diesel products must be hydrogenated prior to rounting to final products. The passage of the Clean Air Act Amendment of 1990 in the U.S.A has forced American refineries to install new facilities to comply with stricter specifications for fuels such as gasoline and diesel oil. Hydrocracking processes are a combination of desulfurization and conversion developed primary to process feeds having a high content of unsaturated hydrocarbons (olefin and polycyclic aromatics) and non-hydrocarbon compounds (sulfur and nitrogen compounds) with a bifunctional catalyst. A variety of bifunctional catalysts and processing designs may be used commercially depending on the feedstock used and desired products. Influence of both feedstock compositions (paraffinic and non-paraffinic vacuum distillate, and wax) and the acidity of bifunctional catalysts on the performance of hydrocracked diesel oil products are discussed briefly in this paper. Low yield or selectivity of diesel oil products by high catalyst acidity, it is suggested that the higher secondary splitting has taken place in converting cracked products into large amounts of low-molecular weight hydrocarbons such as gasoline and LPG. High diesel index product of the paraffinic feedstock due to the high paraffin content of the produced diesel oil.